3/4 x( 5/6 + 2/3)
=3/4 x 3/2
= 9/8
3/2 - 2/3 : 2
=3/2 - 1/3
= 7/6
3/4 x( 5/6 + 2/3)
=3/4 x 3/2
= 9/8
3/2 - 2/3 : 2
=3/2 - 1/3
= 7/6
Tìm x biết :
x + 4/5 = 4/5 + ( 3/7 + 3/5 ) 5/7 + x/35 = 4/5
x < 3/4 + 2 2/3 + 1 < x < 5/6 + 4
x< 5/6 - 3/4 2/3 < x < 2 - 5/6
Tính :
1/3 + 3/4 + 1/2 =
6/8 + 2/4 + 6/24 =
1/2 + 1/3 + 5/6 =
3/5 + 3/2 + 2 =
Tính a) 5/6 x 3/4, 1+2/3 = 3/3 + 2/3 = b) 5/6 - 3/4 =, 1- 2/3=
Tính a) 5/6 x 3/4, 1+2/3 = 3/3 + 2/3 = b) 5/6 - 3/4 =, 1- 2/3=
tính
1/2 + 3/4 - 5/6
( 5/6 + 3/8 ) x 2/7
( 7/6 - 3/4 ) : 3/5
6/7 x 2/3 : 5/7
nhanh lên
Tính bằng hai cách :
( 5/4 + 2/5 ) : 5/6 =
3/4 x 2/5 - 3/4 x 2/7 =
2/3 : ( 5/6 x9/10 ) =
Tính Nhanh
a) ( 1/2 + 1/3 + 1/4 + 1/5 + 1/6 ) - ( 1/2 + 1/3 + 1/4 + 1/5 )
b) ( 2/3 + 2/4 + 2/5 + 2/6 + 2/7 ) - ( 2/4 + 2/5 + 2/6 + 2/7 + 28 )
Bài 3: Tính bằng hai cách
a 1/8 x 5/6 + 5/6 x 2/3
b 7/5 x 3/4 - 1/2 x 3/4
c (5/6 + 5/8) x 2/3
Bài 3: Tính bằng hai cách
a 1/8 x 5/6 + 5/6 x 2/3
b 7/5 x 3/4 - 1/2 x 3/4
c (5/6 + 5/8) x 2/3
Hãy tính 4 1/3 + 3 3/4 + 2 - 2/5 + 8 - 3/5 + 7 - 1/4 + 6 - 2/3